A critical assessment of the Rwandan health financing system: implications for health service utilisation - Hakuzimana, Alex (Department of Public Health and Family Medicine, 2025)
Like many other countries, Rwanda has embraced major health financing reforms to achieve universal health coverage goals and improve access to quality health services without undue financial hardship for its citizens. The public health sector provides most health services in the country, and fragmentation is a major challenge to its health financing system. Literature suggests that fragmentation of health financing may negatively impact the health system's equity, efficiency, and sustainability. Considering the currently available literature, this thesis critically assessed Rwanda's health financing system in relation to the equitable use of health care services, one of the goals of universal health coverage. Various methodological approaches to address different objectives are explored. A case study qualitative approach combining document review and in-depth interviews of key informants indicates that the Rwandan health financing system is fragmented. Using the data from the 2005/2006 and 2010/2011 Integrated Household Living Conditions Surveys, this research shows that despite this fragmentation and contrary to findings from other studies, there was no inequality in public health services use during the two separate periods. These results provide further opportunities for more health sector reforms to improve access to affordable public health services in Rwanda. They also support recommendations to conduct similar analyses to compare these findings with the most recent data to capture the current reality on the equitable use of health care services in public health facilities.